Improved Yorùbá Language Option of the Automated Teller Machine using Translation Equivalence Model - Oyebade, F. O.; Aranuwa, F.O; Adéjùmọ̀, J. A (International Journal of English Language and Translation Studies, 2020)
The introduction of the Automated Teller Machine (ATM) by financial institutions has changed the face of banking globally, Nigeria inclusive. The mechanism has provided a kind of collective sigh-of-relief to both the bank and bank customers, offering convenientt, speedy and round the clock services to bank customers. However, it is not without some inherent challenges as many bank customers who are not proficient in English language found the ATM cumbersome and unfriendly. Attempting to provide solution to these challenges, some banks in Nigeria have developed and introduced the indigenous language version of the Automated Teller Machine options. Yet, user’s response did not reflect the anticipated level of enthusiasm as a result of operational complexities and translation equivalence challenges especially for the Yoruba menu option. In view of this, this work makes an attempt to present an improved translation model introducing Yoruba tone marking to assist those who do not understand the English language, but are monolingual only in Yoruba language to effectively interact with the system. This it is believed, will overcome the challenges of the present design and consequently widen the scope of ATM usage in the interior parts of the country.